The diviners - Bray, Libba; LaVoy, January (New York : Random House/Listening Library, 2012)
Seventeen-year-old Evie O'Neill has been exiled from her boring hometown and shipped off to the bustling streets of New York City. The only catch is that she has to live with her uncle Will and his unhealthy obsession with the occult. Evie worries her uncle will discover her dark secret: a supernatural power that has only brought her trouble. But when police find a murdered girl branded with a cryptic symbol and Will is called to the scene, Evie realizes her gift could help catch a serial killer
Unabridged
Compact disc
Duration: 18:15:00
Producer, Dan Zitt ; director, David Rapkin
Read by January LaVoy; with an introduction read by the author
014-017
Keywords: Teenage girls -- Juvenile sound recordings; Psychic ability -- Juvenile sound recordings; Uncles -- Juvenile sound recordings; Murder -- Juvenile sound recordings; Serial murderers -- Juvenile sound recordings; New York (N.Y.) -- History -- 20th century -- Juvenile sound recordings; Young adult fiction; Occult fiction; Mystery fiction; Paranormal fiction; Detective and mystery stories; Audiobooks; Paranormal fiction; Detective and mystery stories